Morphology, morphometrics, and growth pattern of lemuru fish (Sardinella sp.) landed at TPI Kedonganan, Jimbaran, Bali - Oktavia, Intan; Watiniasih, Ni Luh; Juliantara, I K. Putra (Jurnal Biologi Udayana, 2025)
Indonesia, a nation predominated by water, earning it the designation of a maritime country. It boasts a rich variety of marine life, including numerous fish species. The Bali Waters, part of Indonesia's marine territory, are home to a diverse range of fish species. Lemuru ( Sardinella sp.) is a common fish group found in the southern waters of Bali. These lemuru are typically landed at the Kedonganan Fish Landing Site. Fish residing in specific regions often exhibit unique morphometrics and growth patterns. The objective of this study is to delineate the morphological characteristics and morphometrics of the lemuru fish and to ascertain its growth pattern. Employing direct observation, this research measured variables such as fish morphology, morphometrics encompassing 15 characters, and the growth pattern of the lemuru. Findings reveal that the lemuru's morphological traits observed include a torpedo-like body shape (fusiform), a terminal mouth position, cycloid scales, and a bifurcated caudal fin. The morphometric measurements of lemuru found that the average total length of the fish was of 14.63 cm, so belongs protolan group. The growth pattern analysis of lemuru fish landed at Kedonganan landing site has a b value of 3.4906 (b>3) which means that the growth pattern of lemuru found in Bali sea water is positive allometric.